A Study on the Applicability and Perception Differences of Blockchain Technology in Academic Libraries - Kim, Ho-Won; Noh, Younghee; Roh, Jeong-won (International Journal of Knowledge Content Development & Technology, 2025)
Purpose: This study investigates the impact of blockchain technology on university library management, focusing on perception differences between library professionals and administrators. It aims to explore how factors such as organizational readiness, technical feasibility, adoption barriers, and perceived usefulness affect adoption intentions, particularly in the areas of resource management and digital rights management (DRM). Method : A quantitative difference analysis was conducted using survey data from library practitioners and administrators. Key variables included perceived usefulness, technological benefits, ease of adoption, adoption barriers, and organizational readiness. Findings: Respondents who found blockchain useful for DRM and resource management also rated its technical benefits and ease of adoption more highly. However, perceptions of organizational readiness were low across all groups, indicating concerns over policy support and infrastructure. Implications: For successful blockchain adoption, libraries must strengthen institutional readiness through policy development, infrastructure investment, and staff training. The study offers practical insights for advancing blockchain-based innovations in academic library services.in blockchain-based library innovation.